THE ROLE OF ORGANIZATIONAL CULTURE FOR EMPLOYEE PERFORMANCE: Study on Surabaya City DKP Employees - Susanto, Dedy (International Journal of Multidisciplinary Research and Literature, 2022)
With the formulation of the problem as follows: "Does organizational culture have a significant role in the performance of Surabaya City DKP employees?". To answer the problem formulation mentioned above, the data collection methods are: 1) literature study, and 2) field study; distributing questionnaires and using quantitative data analysis methods, where the researchers used SPSS version 16 with the following research results: The results of distributing questionnaires to 50 respondents from Surabaya City DKP employees which were then processed to obtain the t-count value of the results of data processing with SPSS 16 became identical to 5,670 with a big degree of 0.000 0.05 (smaller than 0.05 = used in the calculation); it can be said that the initial speculation (Ho) is rejected and the opportunity speculation (Ha) is universal. So it may be concluded, that "there is a extensive dating among organizational way of life at the performance of DKP Surabaya town employees".